1972
DOI: 10.1097/00132586-197208000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Pancuronium Bromide (Pavulon). Evaluation of Its Clinical Pharmacology

Abstract: PANCURONIUM BROMIDE IS AN amino steroid muscle relaxant (Figure 1) which was synthesized in 1964 by Hewett and Savage and has been studied and evaluated clinically in Europe during the past four years2 -5 It is an odourless, white, crystalline powder with a bitter astringent taste, melts at 215~ with decomposition, and is soluble in 50 parts of chloroform and one part water at 20~ The co]ourless solution is stable while sealed, but breaks down in a few hours after exposure to air. In Europe it is available in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1972
1972
1974
1974

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…The sequence of muscle paralysis began with the eye, followed by the pharyngeal and laryngeal muscles, the intercostals and lastly the diaphragm. Dobkin et al (1971) found that the duration of action of pancuronium varied considerably with the anaesthetic technique employed, but lasted at least 90 minutes in an average sized fit adult when doses of 0.1 mg/kg were given with a sleep dose of thiopentone (4 to 5 mg/kg) and a halogenated anaesthetic. Similarly, with initial doses of 0.06 to 0.07 mg/kg, Iwatsuki et al (1970) found that apnoea developed within 30 to 150 seconds (mean 80 seconds), whilst the duration of action varied from 40 to 60 minutes.…”
Section: Onset and Duration Ofactionmentioning
confidence: 99%
See 4 more Smart Citations
“…The sequence of muscle paralysis began with the eye, followed by the pharyngeal and laryngeal muscles, the intercostals and lastly the diaphragm. Dobkin et al (1971) found that the duration of action of pancuronium varied considerably with the anaesthetic technique employed, but lasted at least 90 minutes in an average sized fit adult when doses of 0.1 mg/kg were given with a sleep dose of thiopentone (4 to 5 mg/kg) and a halogenated anaesthetic. Similarly, with initial doses of 0.06 to 0.07 mg/kg, Iwatsuki et al (1970) found that apnoea developed within 30 to 150 seconds (mean 80 seconds), whilst the duration of action varied from 40 to 60 minutes.…”
Section: Onset and Duration Ofactionmentioning
confidence: 99%
“…In 465 patients undergoing a variety of surgical procedures, Dobkin et al (1971) reported good operating conditions in approximately 90 % or more of the patients with each anaesthetic technique used (see table II). Among the 4 groups of patients studied (each of which represents a different technique of administering muscle relaxant drugs -see table I), the technique employed in group B had the most cases in which the relaxation was not considered good (18 %).…”
Section: Operating Conditionsmentioning
confidence: 99%
See 3 more Smart Citations